Analysis of Understanding the Concept Using Assignment Techniques on Students' Learning Interest in Irsyadul Islamah Mass PP - Rina Rina; Eva Julyanti (Budapest International Research and Critics University, 2021)
This study aims to analyze conceptual understanding and increase student interest in learning by using assignment techniques in the form of material and SPLDV questions and also an assessment questionnaire. This research uses descriptive qualitative research methods. The subjects who were the research targets were class VIII in MASS PP IRSYADUL ISLAMAH totaling 35 students. The research instrument used was an assignment questionnaire and an interest in learning outcomes. The material is used to provide understanding of the assignment and see the students' interest in learning the assessment subject. Seeing the interest in learning in student assignment techniques in solving problems with SPDLV Mathematics learning questions, students were given an assessment questionnaire on how the teacher applied Mathematics learning. The results of this study indicate that there is an increase in student interest in learning, The increase in research resulted in 11 highest numbers of learning interest, 21 moderate numbers and 3 were in the lowest numbers in student interest in learning. From the results of this study the researchers succeeded in suppressing the lowest number and increasing the highest number of students' understanding and interest in solving problems in learning mathematics. The results of the student's interest in learning obtained an increase in interest in learning by 6.58% in MASS PP IRSYADUL ISLAMAH.